El mapa de vulnerabilidad del acuífero como instrumento de prevención de la contaminación del agua en áreas agrícolas. La cuenca del Arroyo de los Padres (Partido de General Pueyrredón, provincia de Buenos Aires, Argentina) - Viglianchino, Liliana Ester (2023)
The objective of this study is to compare and evaluate the results provided by five methodologies for assessing aquifer vulnerability in an area of intensive agricultural activity in southeastern Buenos Aires, four of them assess intrinsic vulnerability and one specific. The study area is the Arroyo de Los Padres Basin, where the Pampeano aquifer is the sole source of water. The methodologies used include EKv, GOD/GOD-S, and DRASTIC/DRASTIC-P. The aquifer vulnerability assessment was conducted using ArcGIS 10.1 software. In general, it was observed that the most vulnerable zones coincide with the low-lying areas of the basin, while the less vulnerable zones are found in the higher areas. The EKv method identifies over 75% of the study area as having moderate vulnerability, making it the least restrictive and suitable for initial assessments. The GOD and GODS methodologies show a large area classified as "low vulnerability," with GODS indicating low vulnerability in 96% of the territory. DRASTIC and DRASTIC-P reveal greater areas of "high vulnerability." These two methodologies utilize more variables and provide more reliable and realistic results. In summary, the DRASTIC and DRASTIC-P methods are more useful for decision-making and aquifer protection, as they consider important variables related to vulnerability. These methods offer a better balance between uncertainty and utility in decision-making processes.